Modulasi Neurotransmitter pada Gangguan Kognitif Hewan Coba dengan Nanoemulsi Ekstrak Ipomoea aquatica Forsk - Nadiatul Istiqamah Suaka; Salma Ersyara Putri Nugraha; Rizka Arum Pratiwi; Rahmadia Nurafifah; Endang Darmawan (Jurnal Surya Medika (JSM), 2022)
Alzheimer's is a type of dementia characterized by a progressive decline in cognitive function, including all intellectual functions, causing a person to experience difficulties in carrying out daily activities. Ipomoea aquatica Forsk is a plant that has a high antioxidant content that can improve cognitive behavior, memory and increase neurotransmitters. The purpose of this study was to determine the modulating effect of the neurotransmitter nanoemulsion extract of Ipomoea aquatica Forsk on cognitive impairment in experimental animals. This study used 5 groups of mice consisting of a normal control group, a sick control group, a drug control group with two dose levels, namely nanoemulsion extract of Ipomoea aquatica Forsk 200 mg/kg BW and 400 mg/kg BW, and a comparison group, each group consisted of 5 mice. All groups were induced by trimethyltin (TMT) except the normal group. The memory image was obtained from the Morris Water Maze test which was analyzed by one-way repeated measure ANOVA. The Ipomoea aquatica Forsk extract nanoemulsion with a dose of 200 mg/kg BW was able to improve the cognitive function of experimental animals, which was indicated by the Ipomoea aquatica Forsk extract test results showing almost the same MWM results as mice were given donepezil.